Prodia: disruption in clinical laboratory service system - Narolita, Dewita; Darma, Gede Sri (International research journal of management, IT and social sciences, 2020)
The industrial revolution 4.0 has caused disruption in the health care system. The traditional service system into a digital-based service system has shifted slowly. Prodia as the largest laboratory in Indonesia has implemented digital services in an effort to provide the best service for customers and increase customer satisfaction. Digital services developed by Prodia include online results, online order, chatbots, and Prodia mobile apps. This study aims to determine the customer’s response to Prodia’s digital services and obtain feedback from customers to the digital services currently applied. The methodology used is a qualitative method with a case study approach and descriptively analyzed. The results showed that patients gave positive responses to Prodia’s digital services. Some suggestions submitted by customers, including online consultations, online doctor information, added excellence in the application of artificial intelligence, and several policies for patients who already use digital services.